Dextran and Its Derivatives: Biopolymer Additives for the Modulation of Vaterite CaCO3 Crystal Morphology and Adhesion to Cells - Campbell, Jack; Ferreira, Ana M.; Bowker, Laura; Hunt, John; Volodkin, Dmitry; Vikulina, Anna (Advanced Materials Interfaces, 2022)
Nowadays, a great demand for the development of novel drug delivery systems with high potential for bench-to-market transition attracts scientific attention toward materials that are already approved for biomedical use. Here, controlled fabrication of hybrid organic inorganic mesoporous crystals is realized in physiologically relevant conditions by co-synthesis of vaterite CaCO3 in the presence of dextran (DEX) or its functional derivatives. The effects of DEX molecular weight and chemical structure on morphology, porosity, and stability of the hybrids are investigated. Molecular weight of DEX does not affect the crystal growth but leads to the partial blocking of crystal pores. Co-synthesis of DEX functionalized with either carboxymethyl (CM) or diethylaminoethyl (DEAE) groups drastically increased crystal porosity without influencing crystal size. pH-dependent vaterite-to-calcite recrystallization is significantly suppressed by inclusion of carboxymethyl-dextran (CM-DEX), making vaterite crystals stable in acidic medium, whereas the incorporation of diethylaminoethyl-dextran (DEAE-DEX) has no effect. The hybrids prepared with charged DEX derivatives possess stronger adhesion to normal human dermal fibroblasts: three times higher crystal adherence compared to pristine crystals. These results provide fundamental physical–chemical insights into the crystallization of DEX/vaterite hybrids and are discussed in view of the potential of these functional delivery carriers for biomedical and other applications.
CRIS-Team Scopus Importer:2022-10-07
Keywords: biomineralization; co-synthesis; drug delivery; mesoporous; recrystallization